2013
DOI: 10.1523/jneurosci.0530-13.2013
|View full text |Cite
|
Sign up to set email alerts
|

TNF-α Downregulates Inhibitory Neurotransmission through Protein Phosphatase 1-Dependent Trafficking of GABAAReceptors

Abstract: Inflammation has been implicated in the progression of neurological disease, yet precisely how inflammation affects neuronal function remains unclear. Tumor necrosis factor-␣ (TNF␣) is a proinflammatory cytokine that regulates synapse function by controlling neurotransmitter receptor trafficking and homeostatic synaptic plasticity. Here we characterize the mechanisms through which TNF␣ regulates inhibitory synapse function in mature rat and mouse hippocampal neurons. Acute application of TNF␣ induces a rapid a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
145
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 199 publications
(152 citation statements)
references
References 114 publications
6
145
0
1
Order By: Relevance
“…TNFa is a glial-derived factor that was first described in in vitro studies to be required for homeostatic upscaling of excitatory synaptic transmission and downscaling of inhibitory synaptic transmission, but not involved in Hebbian LTP and LTD [122][123][124][125]. Its role in homeostatic plasticity was further confirmed in vivo, where TNFa knockout mice display typical Hebbian weakening of visual cortical responses following brief MD, but fail to exhibit the normal delayed homeostatic rebound [45].…”
Section: (B) Distinct Players In Homeostatic Plasticitymentioning
confidence: 96%
“…TNFa is a glial-derived factor that was first described in in vitro studies to be required for homeostatic upscaling of excitatory synaptic transmission and downscaling of inhibitory synaptic transmission, but not involved in Hebbian LTP and LTD [122][123][124][125]. Its role in homeostatic plasticity was further confirmed in vivo, where TNFa knockout mice display typical Hebbian weakening of visual cortical responses following brief MD, but fail to exhibit the normal delayed homeostatic rebound [45].…”
Section: (B) Distinct Players In Homeostatic Plasticitymentioning
confidence: 96%
“…43,44 In this context, it seems noteworthy that acute application of tumor necrosis factor-α downregulates inhibitory synaptic transmission via the protein phosphatase 1-dependent trafficking of GABA A receptors. 46 In addition to phosphorylation, gephyrin is subject to palmitoylation 47 (Figure 1). Gephyrin was initially postulated as a potential substrate for palmitoyl acyltransferase, 48 and later work confirmed that cysteine 212 and cysteine 284 are palmitoylated by the enzyme, Asp-His-His-Cys (DHHC)-12, which is localized to the Golgi apparatus and dendritic shaft, and directly interacts with gephyrin.…”
Section: Posttranslational Modificationsmentioning
confidence: 99%
“…It is based on Ca 2+ -dependent negative feedback mechanisms and aims at adjusting synaptic strength to perturbations in neuronal activity (Turrigiano, 2012;Vitureira et al, 2012;Davis, 2013). If for example network activity is reduced, neurons will respond with a slow adaptive, i.e., homeostatic increase in excitatory synaptic strength (or the compensatory down-scaling of inhibitory synapses; e.g., Pribiag and Stellwagen, 2013;Vlachos et al, 2013c). Likewise, increased network-activity will cause the down-regulation of excitatory synaptic strength and an increase in inhibitory synaptic drive.…”
Section: The Role Of Homeostatic Synaptic Plasticity In Pathological mentioning
confidence: 99%